Frequencies of Blood Group Systems MNS, Diego, and Duffy and Clinical Phases of Carrion’s Disease in Amazonas, Peru - Oscar Acosta; Luis Solano; Jorge Escobar; Miguel Fernandez; Carlos Solano; Ricardo Fujita (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Carrion’s disease (CD), is a human bartonellosis, that is, endemic in the Andes of Peru, Ecuador, and Colombia. Bartonella bacilliformis, a native hemotrophic bacteria, is the causative agent of CD, and the interaction with the host could have produced changes in the gene frequencies of erythrocyte antigens. The goal here is to investigate the relationship between allele frequencies of blood group systems MNS, Diego, and Duffy and the clinical phases of CD, within a genetic context. In this associative and analytical study, 76 individuals from Bagua Grande, the province of Utcubamba, and the department of Amazonas in Peru, were enrolled. Forty of them resided in Tomocho-Collicate-Vista Hermosa area (high prevalence of cases in chronic phase, verrucous, or eruptive phase, without previous acute phase). Thirty-six individuals were from the area of Miraflores (high prevalence of cases in acute phase only) and were evaluated for blood group systems MNS, Diego, and Duffy. This study constitutes one of the first attempts at evaluating the genetic factors and clinical phases of CD. No significant statistical differences (P>0.05) between allele frequencies of blood groups MNS, Diego, and Duffy and the prevalence of chronic and acute phases were detected in the two areas of Amazonas, Peru.